2021
DOI: 10.3390/ijms22094646
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Targets of Manganese-Induced Neurotoxicity: A Five-Year Update

Abstract: Understanding of the immediate mechanisms of Mn-induced neurotoxicity is rapidly evolving. We seek to provide a summary of recent findings in the field, with an emphasis to clarify existing gaps and future research directions. We provide, here, a brief review of pertinent discoveries related to Mn-induced neurotoxicity research from the last five years. Significant progress was achieved in understanding the role of Mn transporters, such as SLC39A14, SLC39A8, and SLC30A10, in the regulation of systemic and brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(31 citation statements)
references
References 211 publications
(246 reference statements)
1
28
0
2
Order By: Relevance
“…Multiple genetic and environmental variables contribute to the onset and progression of Parkinson's disease, which is related with the degradation of DAergic neurons in the substantia nigra pars compacta [31]. Indeed, epidemiological studies have connected the development of neurodegeneration to Mn toxicity [22][23][24]51,52]. This can be mediated by impairment of protein metabolism, according to findings in nonhuman models [25,34,35].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple genetic and environmental variables contribute to the onset and progression of Parkinson's disease, which is related with the degradation of DAergic neurons in the substantia nigra pars compacta [31]. Indeed, epidemiological studies have connected the development of neurodegeneration to Mn toxicity [22][23][24]51,52]. This can be mediated by impairment of protein metabolism, according to findings in nonhuman models [25,34,35].…”
Section: Resultsmentioning
confidence: 99%
“…These processes are potentially connected to 1522 diseases, of which 21 are associated with the nervous system [49]. Other functional and omics studies [25][26][27][28]34,35] have identified these potential mechanisms of Mn-induced neurotoxicity, reviewed by Tinkov et al [52]. In line with this, using microarray analysis and systems biology approaches, we verified a connection between Mn-induced acute cytotoxicity in the RA-differentiated SH-SY5Y-DAergic cell model and impairment of several pathways, including protein synthesis (18 processes), cell metabolism (10 processes), cell signaling (3 processes), neurodevelopment (1 process), and neurodegeneration (3 processes) (Tables 2 and 3).…”
Section: Discussionmentioning
confidence: 99%
“…Mn can interfere with the dopaminergic, cholinergic, glutamatergic, and GABAergic systems [78][79][80]. Mn disturbs these neurotransmitter systems through multiple mechanisms including the direct interaction with neurotransmitter receptors.…”
Section: Manganesementioning
confidence: 99%
“…Mn also induces endoplasmic reticulum stress, which can lead to apoptosis and autophagy deregulation [37,38]; neuroinflammation, astrocytes being the main mediators of the proinflammatory effects of the metal [19,39]; alterations in cell signaling such as AKT, JNK, and other insulin-like pathways (this last one in Caenorhabditis elegans) [19,40,41]; and epigenetic alterations by increasing DNA methylation and histone acetylation in different models in vitro and in vivo [40][41][42]. Mn also interferes with GABAergic and catecholaminergic neurotransmissions by reducing the production of the neurotransmitters.…”
Section: A Brief Introduction To Mn Neurotoxicity: Gut-independent Mechanismsmentioning
confidence: 99%
“…Several mechanisms by which Mn causes neurotoxicity have been unraveled, but it is still considered poorly understood. Multiple analyses of pathways affected by Mn exposure using metallomics, proteomics, gene expression, and bioinformatics revealed that Mn exposure alters several processes such as proteostasis, cell metabolism and signaling, immunity and inflammation, cell cycle, and neurodegeneration-associated pathways [ 19 ]. It is well established that Mn accumulates in areas rich in dopaminergic neurons.…”
Section: A Brief Introduction To Mn Neurotoxicity: Gut-independent Mechanismsmentioning
confidence: 99%